ENERGY DECOMPOSITION ANALYSIS AND NATURAL ORBITAL FOR CHEMICAL VALENCE OF W-E BONDING IN W(CO)4 COMPLEXES WITH TETRYLENE LIGANDS [(CO)4WNHE] (E = C – Pb) - Ai Nhung, Nguyen Thi; Ly, Nguyen Van; Dien, Do; Tat, Pham Van (Vietnam Journal of Science and Technology, 2014)
The natural of W-E bonding in group 14 compounds [(CO)4W-NHE] has been investigated by means of the energy decomposition analysis- natural orbital for chemical valence (EDA-NOCV) method which combines charge (NOCV) and energy (EDA) partitioning schemes at the BP86/TZ2P+ level of theory. The EDA-NOCV indicates that the decrease in bond strength from W4-NHC to W4-NHPb correlates with the decrease of DEelstat and DEorb. The EDA-NOCV calculations suggest that the trend of the W-E bond strength was W4-NHC > W4-NHSi > W4-NHGe > W4-NHSn > W4-NHPb. The decrease in the donation (CO)4W¬ NHE, which is manifested in the calculated values for DEs and in the electrostatic attraction, DEelstat , provides a rationale for the weaker bonding of the heavier atoms E. The bonding in the complexes with N-heterocyclic carbene and analogues W4-NHE exhibits the typical feature in terms of strong s-donation and weak p-donation.